A new method to evaluate breaststroke kicking technique using a pressure distribution analysis - Tsunokawa, T.; Nakashima, M.; Sengoku, Y.; Tsubakimoto, S.; Takagi, H. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The propulsive force produced by limbs is a key contributor to the velocity attained during human swimming. However, the swimming motion in the aquatic environment is very complex, being difficult to evaluate the propulsive forces. Although many researchers have developed direct method to measure active drag during human swimming (Hollander et al. 1986; Formosa, Mason & Burkett 2011), the situation differs from that in free swimming. To circumvent these difficulties, a new method has been developed in which fluid forces are estimated from analysis of pressure distributions (Takagi & Wilson 1999; Kudo et al. 2008). This method has been used to successfully measure the force acting on a hand over time. As swimmers move their hand through the water, the pressure fluid drag forces act perpendicularly to the hand surface. Swimmers are propelled by the reaction force that matches the sum of these fluid forces. Estimating fluid forces by analyzing pressure distributions confers a distinct advantage over conventional measures: swimming technique is undisturbed and, provided that the pressure drag is measured directly, errors in the estimated fluid forces appear to be reduced. However, no methodology has been proposed for predicting the fluid forces acting on other parts of a swimmer's body. Especially in the breaststroke, the propulsive forces produced by lower limb motions are more important than those produced by upper limb motions. Therefore, while an improved kicking technique would seem to be essential to performance of the breaststroke. If the fluid forces produced by breaststroke kicking could be measured precisely, coaches and swimmers would be better equipped to evaluate their technical training. In addition, if the reliability of a methodology for estimating the fluid forces acting on a foot during breaststroke kicking could verified, then coaches and swimmers could apply this information. The purpose of this study was to develop a new method for evaluation of breaststroke kicking motion using a pressure distribution analysis around a foot.